2003
DOI: 10.1111/j.1532-5415.2004.52005.x
|View full text |Cite
|
Sign up to set email alerts
|

Can a Short Period of Micronutrient Supplementation in Older Institutionalized People Improve Response to Influenza Vaccine? A Randomized, Controlled Trial

Abstract: A micronutrient supplement providing the reference nutrient intake administered over 8 weeks had no beneficial effect on antibody response to influenza vaccine in older people living in long-term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…, 2002; Barringer et al. , 2003; Allsup et al. , 2004; The Writing Group of the MAVIS Trial Group, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…, 2002; Barringer et al. , 2003; Allsup et al. , 2004; The Writing Group of the MAVIS Trial Group, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Improving nutritional status, broadly defined, has been studied as a means to improve immune response to influenza vaccination, particularly among older individuals who may have reduced antibody response and poor nutritional status compared to younger individuals. Most studies have involved supplementation with a combination nutritional formula, primarily antioxidant-based, but results have been mixed with some studies describing a beneficial effect on antibody response [21, 22] and others reporting no effect [23, 24]. In general, these studies were of relatively short duration, and included frail or elderly subjects residing in nursing homes or long term care facilities; these studies did not investigate the independent effect of weight status per se , making it difficult to draw comparisons with our results.…”
Section: Discussionmentioning
confidence: 99%
“…We have however been unable to detect any improvement in sero-conversion by one month's supplementation with a balanced trace element and vitamin preparation. 76 Taken overall, a meta-analysis showed that there is little if any benefit from a multivitamin and mineral supplement, in terms of incidence of infections in an elderly population, 77 and this has recently been confirmed in a large free living population in Scotland. 78 Cognitive function It has long been thought that supplements of vitamins and trace elements may improve aspects of cognitive function, and studies of well school children have suggested that concentration ability may be improved as a result of such supplements.…”
Section: Infections In the Elderly Populationmentioning
confidence: 99%